Web reasoning and rule systems : 9th International Conference, RR 2015, Berlin, Germany, August 4-5, 2015, Proceedings /: 9th International Conference, RR 2015, Berlin, Germany, August 4-5, 2015, Proceedings. (2015) - Unknown
No abstract available